Réinventer le commerce de bouche dans la ville postsocialiste : le cas de Prague - Aurore Navarro (Belgeo)
The research is tracking the process of recomposition and renovation of the supply in the artisanal food retail trade at the city center of Prague which particularity consists from the early 2010 in the proliferation of boutique-food shops (bakery, butcher shops, cheese dairy,…). The vocabulary and the symbolic universe borrowed by those new places of consumption in their promotional documents and trade strategies work with notions of authenticity, quality, long history and tradition. The claim for a historic continuity wants to ignore the impact of the regime of real-socialism or the concentration of productive activities in the State or collective companies usually of big dimension that caused mostly total extinction of independent trade. By an empiric methodological approach, the author of the paper identifies the stakeholders of the renewal, their strategies of localisation and development in the city.